Latest developments in Russian imports of sanctioned technology products - Heli Simola (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2023)
This brief examines the latest developments in Russian imports on the basis of mirror statistics. We focus particularly on technology products subject to export restrictions imposed by sanctioning coalition countries. While most Russian imports of technology products subject to sanctions fell considerably between the first half of 2021 and the first half of 2023, our analysis reveals that the value of certain imported technology products also increased substantially. Exports of these products grew dramatically particularly from Central Asia and Caucasus, but the share of these countries in Russian imports is still moderate. China was by far the most important provider of technology products to Russia in absolute terms during the observation period.
urn:nbn:fi-fe20231129150248
Keywords: 330; Russia; imports; sanctions